UJI AKTIVITAS ANTIOKSIDAN DAN PENENTUAN KANDUNGAN ANTOSIANIN TOTAL KULIT BUAH MANGGIS (Garcinia mangostana L) - Wiwin Supiyanti; Endang Dwi Wulansari; Lia Kusmita (Majalah Obat Tradisional, 2010)
Mangosteen fruit with latin name Garcinia mangostana L. got the nickname Queen of tropical fruit (Tropical Fruits queen). Most of the mangosteen fruit is consumed in fresh condition. Mangosteen rind purple black. Mangosteen rind allegedly containing anthocyanin compounds. This study aimed to determine antioxidant activity of bark extracts of the mangosteen fruit and the total anthocyanin content in the rind of the mangosteen fruit. Object of research is that the mangosteen rind has been good to consume. Mangosteen rind mashed and then soaked with methanol containing 1% HCl. Antioxidant activity test mangosteen rind extract includes a qualitative test of antioxidant activity of extracts of TLC plates sprayed mangosteen rind 0.1 mM DPPH reagent produces patches of pale yellow with a purple background. Quantitative test of antioxidant activity based on the parameters EC50 using DPPH method with the comparison of vitamin C. Obtained EC50 value of 8.5539 tg/mL and EC50 values of vitamin C is 3.3676 tg/mL. Average total anthocyanin content in the skin of the mangosteen fruit is 59.3 mg in 100 grams of the mangosteen rind.